Instructional language and the performance of UiTM Cawangan Pahang DIS students in physics courses / Ahmad Saat - Saat, Ahmad (Universiti Teknologi MARA Cawangan Pahang, 2003)
A study was carried out to investigate the performance in physics courses of UiTM Cawangan Pahang Diploma in Science (DIS) students before and after the introduction of English as the medium of instruction. The focus was on three courses taught each in the first three semester of their study. Their codes are PHY104, PHY154 and PHY204. The sets of students studied were those sitting the October 1998, April 1999 and October 1999 examinations, which represent students taught in Bahasa Malaysia, and the April 2000, October 2000 and April 2001 examinations, which represent students taught in English. Data for the study were obtained from the Academic Affair Section UiTM Cawangan Pahang, and analyzed using SPSS. The results showed that for PHY104 and PHY204 there is negative effect on students' performance after the adoption of English as the medium of instruction. How for PHY154 it was found that language of instruction did not influence students' performance in that course.